Preparation method and application of MXene-MOFs heterostructure material
By preparing MXene-MOFs heterostructured gas sensing material, the problem of difficulty and cost of detecting trace ammonia gas in the prior art is solved, and a fast, sensitive and low-cost NH3 gas detection is achieved.
Patent Information
- Application Number
- CN202311258286.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to detect trace ammonia gas quickly and sensitively, especially in food safety and environmental monitoring, which has problems of difficulty and high cost.
By preparing a MXene-MOFs heterostructure gas sensing material, using its unique two-dimensional structure and large specific surface area, combined with electron recombination at the heterostructure interface, rapid detection of trace NH3 gas is achieved.
It realizes fast and sensitive detection of NH3 gas, is cheap and easy to operate, and is suitable for food safety and environmental monitoring and other fields.
Smart Images

Figure CN119708511A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method and application of a MXene-MOFs heterostructure material, belonging to the technical field of nano-functional materials and environmental monitoring. Background Art
[0002] Ammonia (NH3), as one of the common volatile organic compounds (VOCs), is commonly found in all aspects of industrial production. However, this organic compound is harmful to the human body and has an irritating effect on the skin, mucous membranes and upper respiratory tract. The main symptoms are irritation of the eyes, nose and throat, headache, dizziness, drowsiness and gastrointestinal dysfunction. In addition, among all biomarkers of food safety, NH3 is crucial for meat spoilage monitoring and is also one of the sources of the pungent smell of decay. The detection of NH3 has been widely used in the food industry, such as the assessment of air quality in livestock houses and the freshness of meat products. However, meat products often undergo long-distance transportation from the place of origin to the marketing point, which makes it more difficult to evaluate meat quality in real time. Therefore, there is an urgent need to develop a sensor to solve these problems.
[0003] Detection of NH3 gas is a reliable method to monitor meat quality. Various sensing methods for NH3 have been studied, and semiconductor-based gas sensors are widely used due to their advantages such as good stability, low cost, and high sensitivity.
[0004] The core of gas sensors is the design and preparation of gas-sensitive materials. In recent years, MXene-based materials have attracted extensive attention from researchers due to their excellent conductivity and large specific surface area. In addition, MXene is obtained through chemical etching of the MAX phase, so there will be a large number of chemical functional groups on MXene, and a large number of dangling bonds at the end groups. These rich chemical functional groups and dangling bonds have greatly increased the types of MXene-based composite materials and provided an excellent platform for their molecular design. The modification and compounding of MXene materials are conducive to expanding the application scenarios of the MXene material family and providing new ideas and strategies for the preparation of new gas sensing materials. Summary of the invention
[0005] In recent years, the rise and rapid development of artificial intelligence (AI) and the Internet of Things (IoT) have made the "smart earth" no longer a conceptual concept. Sensing technology is an important technical means to achieve information perception and collection. It is the bottom of the IoT architecture and the foundation of the upper structure (network construction layer, management service layer and comprehensive application layer). In the rich and complex sensor system, gas sensors have important application value and wide application needs in many fields, such as environmental protection, food safety, agricultural production, medical health, national defense security, etc.
[0006] The three factors that affect the performance of oxide semiconductor gas sensors are: recognition function, conversion function, and utilization rate of sensitive bodies. The recognition function reflects the strength of the interaction between the sensitive material and the gas molecules to be measured. It refers to the ability of the sensitive material to recognize the gas molecules to be measured. The strength of the recognition function is closely related to the surface of the material. The conversion function refers to the ability of the sensitive material used to convert the concentration signal of the gas to be measured into a resistance signal. The conversion function is closely related to the grain size, crystallinity, and carrier mobility of the sensitive material. The utilization rate of the sensitive body refers to the proportion of the part of the sensitive body that undergoes resistance change in the gas to be measured to the entire sensitive body. It is usually closely related to the porosity and dispersion of the sensitive material.
[0007] The core of gas sensors is the sensing material, which is the "central brain" of the sensor. Therefore, the development and preparation of sensing materials is the key to improving gas sensing performance. In the development process of gas sensing materials, the design of the specific surface area of the material is particularly critical. MXene, as an emerging two-dimensional nanostructure, has a large specific surface area. In addition, its excellent conductivity also makes it a good material carrier.
[0008] Metal-organic frameworks (MOFs) are crystalline porous materials self-assembled by metal ions / clusters and organic ligands through coordination bonds. They have been a hot topic in the field of chemistry and materials science in recent decades. Compared with traditional inorganic materials, MOFs have the characteristics of larger specific surface area, higher porosity, diverse structural types and adjustable functions. In addition, the rich variety of organic ligands and metal nodes make MOFs highly plastic in terms of charge, polarity, chirality, redox potential, photoactivity, hydrophobicity / hydrophilicity, aromaticity / lipophilicity, stereochemistry, etc. Combining two-dimensional MXene with porous MOFs can realize the construction of materials with larger specific surface area, which is beneficial to the gas mass transfer process and improves the gas sensing performance.
[0009] The purpose of the present invention is to provide a method for preparing a MXene-MOFs heterostructure gas sensing material with low cost and simple operation, and to use the heterostructure in a gas sensor to achieve rapid and sensitive detection of trace NH3 in production and life.
[0010] Based on this purpose, the present invention firstly prepares a new type of MXene-MOFs heterostructure gas sensing material, and utilizes the unique two-dimensional structure, large specific surface area and electronic recombination at the heterostructure interface of the material to realize the detection of trace NH3 gas.
[0011] According to one aspect of the present application, a method for preparing a MXene-MOFs heterostructure material is provided, the preparation method comprising the following steps:
[0012] (1) A mixture containing Ti3AlC2 and an etchant is stirred, washed, centrifuged, and dried to obtain an accordion-shaped MXene;
[0013] (2) The obtained mixture II of accordion-shaped MXene, Cu precursor, H2BDC, and solvent is reacted, centrifuged II, washed II, and dried II to obtain a MXene-MOFs heterostructure material.
[0014] Optionally, the mass volume ratio of the Ti3AlC2 to the etchant is 0.5-1 g: 10-50 mL.
[0015] Optionally, the etchant includes HCl, HF and water.
[0016] Optionally, the volume ratio of HCl, HF and water is 1:1:1.
[0017] Optionally, in step (2), the Cu precursor is selected from at least one of cupric chloride, copper acetylacetonate, copper acetate and copper nitrate.
[0018] Optionally, the mass ratio of the Cu precursor to the H2BDC is 0.5:1 to 1:0.5.
[0019] Optionally, the mass ratio of the Cu precursor to the H2BDC is selected from any value of 0.5:1, 1:1, 1:0.5, or a range between any two of the above.
[0020] Optionally, the mass volume ratio of the accordion-shaped MXene to the solvent is 0.5-1 g: 0.5-1 mL.
[0021] Optionally, the mass ratio of the accordion-shaped MXene to the Cu precursor is 1:1.
[0022] Optionally, the solvent is selected from at least one of ethanol, N,N-dimethylformamide and methanol.
[0023] Optionally, the solvent is N,N-dimethylformamide, and the amount of N,N-dimethylformamide used is 10 to 25 mL.
[0024] Optionally, in step (1), the stirring temperature is 40 to 90° C., and the stirring time is 16 to 24 hours.
[0025] Optionally, the stirring temperature is selected from any value of 40°C, 45°C, 50°C, 55°C, 60°C, 90°C or a range between any two of the above values.
[0026] Optionally, the stirring time is selected from any value among 16h, 18h, 20h, 22h, 24h or a range between any two of the above.
[0027] Optionally, in step (2), the reaction temperature is 50 to 100° C., and the reaction time is 12 to 24 hours.
[0028] Optionally, the reaction temperature is selected from any value of 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or a range between any two of the above values.
[0029] Optionally, the reaction time is selected from any value among 12h, 16h, 18h, 20h, 22h, 24h or a range between any two of the above.
[0030] Optionally, the temperatures of drying I and drying II are independently selected from 50 to 85° C., and the times of drying I and drying II are independently selected from 6 to 12 hours.
[0031] Optionally, the number of centrifugation I and centrifugation II is independently selected from 3 to 7 times.
[0032] Optionally, the solvents for washing I and washing II are independently selected from at least one of water, ethanol and methanol.
[0033] According to another aspect of the present application, a MXene-MOFs heterostructure material prepared by the preparation method described above is provided, and the MXene-MOFs heterostructure material has a two-dimensional lamellar structure.
[0034] Optionally, the content ratio of MXene to MOFs in the MXene-MOFs heterostructure material is 1:5% to 30%.
[0035] Optionally, the content ratio of MXene to MOFs in the MXene-MOFs heterostructure material is selected from any value of 1:5%, 1:10%, 1:15%, 1:20%, 1:25%, 1:30% or a range between any two of the above.
[0036] According to another aspect of the present application, there is provided an application of the above-mentioned MXene-MOFs heterostructure material in an NH3 gas sensor.
[0037] Optionally, the detection limit of the NH3 gas sensor for NH3 is 460-600 ppb.
[0038] Optionally, the detection limit of the NH3 gas sensor for NH3 is selected from any value of 460ppb, 480ppb, 500ppb, 520ppb, 540ppb, 580ppb, 600ppb or a range between any two of the above values.
[0039] Optionally, the operating temperature of the NH3 sensor is 25-35°C.
[0040] As a specific implementation, the present invention is implemented by the following technical solutions:
[0041] 1. Preparation of a MXene-MOFs heterostructure gas sensing material and its application in NH3 gas sensing, the preparation method comprising the following preparation steps:
[0042] Step a, preparing MXene-MOFs heterostructure gas sensing materials;
[0043] Step b, constructing an NH3 gas sensor;
[0044] Among them, the specific steps of step a for preparing MXene-MOFs heterostructure gas sensing materials are:
[0045] (1) Preparation of MXene
[0046] A certain amount of Ti3AlC2 is added to a mixed etchant solution consisting of a certain amount of HCl, HF and deionized water (DI water). The mixture is stirred at 40-60°C for 16-24h. The product is then repeatedly washed with DI water until the pH is neutral, centrifuged and dried to obtain an accordion-shaped MXene.
[0047] (2) Preparation of MXene-MOFs heterostructures
[0048] The product obtained in (1) was dissolved in a certain amount of DMF and stirred to obtain a uniform system. A certain amount of Cu precursor was then added to the mixed solution and stirred evenly to obtain a uniform system. A certain amount of H2BDC was then added and stirred to completely dissolve it and to mix with Cu. 2+ The mixed solution is then transferred to a reactor, and after the reaction is completed, the product is collected, centrifuged, washed, and dried to obtain a MXene-MOFs heterostructure.
[0049] Step b: The specific construction steps for constructing the NH3 gas sensor are:
[0050] (1) Using the interdigital electrode as the gas sensing electrode, add the prepared sample to an appropriate amount of solvent and mix to form a uniform slurry. Evenly drop the slurry on the electrode surface to form a film. Dry the interdigital electrode in an oven to evaporate the solvent to obtain a sensing film.
[0051] (2) The electrode obtained in step (1) is then aged in an oven to remove the organic solvent remaining on the electrode, thereby obtaining a gas sensing electrode with stable resistance. The gas sensing electrode is connected to a test instrument to obtain an NH3 gas sensor.
[0052] Optionally, in step (1), the solvent is selected from at least one of ultrapure water, anhydrous ethanol, and acetone.
[0053] 2. The gas sensor based on the two-dimensional metal oxide gas sensitive material is applied to the detection of NH3 gas molecules, and its characteristics are that the specific detection method is:
[0054] (1) Using interdigital electrodes as gas sensing electrodes, 5-10 μL of slurry was dropped onto the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrodes were dried at 65-100°C to form a sensing film.
[0055] (2) The modified interdigital electrode is heated in an oven to 180-200° C. for 12-24 hours to remove the residual organic solvent, thereby obtaining the NH 3 gas sensor to be tested.
[0056] (3) The gas sensor test is carried out using the static gas distribution method, that is, a certain amount of NH3 liquid is evaporated on a hot stage using a micro-injector to obtain a certain concentration of NH3 gas. The vaporized NH3 gas evaporates in the test chamber, and the NH3 gas molecules are detected by recording the resistance change of the sensor before and after the gas is introduced.
[0057] (4) Record the initial resistance of the sensor in air as R a , different concentrations of NH3 are introduced into the test chamber, and the resistance when the gas is introduced is recorded as R g , with R g With R a Draw a working curve based on the relationship between the ratio and the concentration of NH3 gas molecules.
[0058] The main advantages of this approach are:
[0059] (1) The preparation method is simple. Through simple liquid-phase chemical reactions, the rich functional groups and dangling bonds on the MXene surface are used as attachment sites for MOFs to achieve the preparation of MXene-MOFs heterostructures.
[0060] (2) The preparation method is controllable. This method provides a preparation strategy for MXene-MOFs heterostructures. By changing the added central ions and ligands, the growth of different MOFs structures can be achieved.
[0061] (3) The MXene-MOFs structure exists in the form of a heterojunction. The existence of the heterojunction can greatly improve the gas sensing performance. In addition, the large specific surface area of MOFs is conducive to gas adsorption and mass transfer. The synergistic effect of the two has greatly improved the gas sensing performance. In summary, the simple and effective preparation of this material has important scientific significance and application value.
[0062] (4) The present invention is the first to apply MXene-MOFs heterostructure gas sensing materials to the preparation of NH3 gas sensors. The porous structure of MOFs increases the BET surface area of the material and provides more reactive sites for gas molecules. The heterostructure formed by MOFs and MXene increases the accessibility of the composite material to the target gas molecules, thereby improving the sensing performance.
[0063] The present invention also provides a technical reference for related sensors, such as photoelectrochemical sensors, electrochemical sensors, etc., and has a wide range of potential use value.
[0064] The beneficial effects of this application include:
[0065] 1) The NH3 gas sensor described in the present application is simple to prepare and easy to operate, and can achieve rapid, sensitive, and highly selective detection of NH3 gas molecules at a low cost. In addition, the test conditions close to room temperature provide conditions for portable detection of the sensor, which has market development prospects.
[0066] 2) The present application provides a method for preparing a MXene-MOFs heterostructure. The preparation method is simple and uses a "one-pot method" to achieve controllable preparation of the material.
[0067] 3) This application uses the abundant functional groups and dangling bonds on the MXene surface as the loading sites of MOFs to achieve the in situ growth of MOFs structure on the MXene surface. This method is universal and can realize the synthesis of different MXene-MOFs structures, providing a new strategy for the preparation of gas sensing materials.
[0068] 4) This application realizes the construction of MXene-MOFs two-dimensional heterostructure by electrostatic adsorption method, and uses it in ultra-sensitive gas sensing detection, realizing the detection of NH3 at room temperature. The constructed sensor has the characteristics of high sensitivity, fast response recovery speed, and good selectivity. The hierarchical two-dimensional structure between layers ensures effective electron transfer. In addition, the introduction of Cu-BDC can significantly avoid the aggregation of MXene and improve the gas-sensitive response performance of the material. The successful preparation of this material also provides a technical reference for related chemical sensors, such as electrochemiluminescence sensors, electrochemical sensors, etc., and has a wide range of potential use value. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a working curve diagram of the MXene-MOFs heterostructure gas sensing material prepared in Example 1 of the present application.
[0070] Figure 2 This is a selectivity diagram of the gas sensor prepared in Example 12 of the present application. DETAILED DESCRIPTION
[0071] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0072] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0073] In the examples of this application, the instruments used to characterize the MXene-MOFs heterostructure gas sensing material are as follows:
[0074] Instrument Model Manufacturer RX I Fourier Transform Infrared Spectrometer Perkin Elmer Model Smart Lab SE XRD Nippon Rigaku Co., Ltd. Gemini 300 Field Emission Scanning Electron Microscope Carl Zeiss AG Optical and electrical integrated test platform CGS-MT KQ3200DB CNC Ultrasonic Cleaner Kunshan Ultrasonic Instrument Co., Ltd.
[0075] Example 1 Preparation of MXene-MOFs heterostructure gas sensing materials
[0076] (1) Preparation of MXene
[0077] 0.5 g of Ti3AlC2 was added to a mixed etchant solution consisting of 1 mL of HCl, 1 mL of HF, and 1 mL of deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 °C for 16 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 3 times, and dried at 50 °C for 12 h to obtain an accordion-shaped MXene.
[0078] (2) Preparation of MXene-MOFs heterostructures
[0079] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.5 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.5 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 60°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.5:0.5, respectively.
[0080] Example 2 Preparation of MXene-MOFs heterostructure gas sensing materials
[0081] 1) Preparation of MXene
[0082] 0.5 g of Ti3AlC2 was added to a mixed etchant solution consisting of 2 mL of HCl, 2 mL of HF, and 2 mL of deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 °C for 12 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 5 times, and dried at 50 °C for 5 h to obtain an accordion-shaped MXene.
[0083] (2) Preparation of MXene-MOFs heterostructures
[0084] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.5 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.5 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 80°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.5:0.5, respectively.
[0085] Example 3 Preparation of MXene-MOFs heterostructure gas sensing materials
[0086] 1) Preparation of MXene
[0087] 0.5 g of Ti3AlC2 was added to a mixed etchant solution consisting of 3 mL of HCl, 3 mL of HF, and 3 mL of deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 80 °C for 8 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 4 times, and dried at 60 °C for 5 h to obtain an accordion-shaped MXene.
[0088] (2) Preparation of MXene-MOFs heterostructures
[0089] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.4 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.4 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged 4 times, washed with ethanol solvent, and dried at 80°C for 7 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.6:0.4, respectively.
[0090] Example 4 Preparation of MXene-MOFs heterostructure gas sensing materials
[0091] 1) Preparation of MXene
[0092] 0.5 g of Ti3AlC2 was added to a mixed etchant solution consisting of 4 mL of HCl, 4 mL of HF, and 4 mL of deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 ° C for 15 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 5 times, and dried at 80 ° C for 12 h to obtain an accordion-shaped MXene.
[0093] (2) Preparation of MXene-MOFs heterostructures
[0094] The product obtained in (1) was dissolved in 15 ml of DMF and stirred to obtain a uniform system. Then 0.3 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.3 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged four times, washed with ethanol solvent, and dried at 70°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.7:0.3, respectively.
[0095] Example 5 Preparation of MXene-MOFs heterostructure gas sensing materials
[0096] 1) Preparation of MXene
[0097] 1.0 g of Ti3AlC2 was added to a mixed etchant solution consisting of 5 mL HCl, 5 mL HF, and 5 mL deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 ° C for 12 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 5 times, and dried at 70 ° C for 5 h to obtain an accordion-shaped MXene.
[0098] (2) Preparation of MXene-MOFs heterostructures
[0099] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.2 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.2 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 80°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.8:0.2, respectively.
[0100] Example 6
[0101] 1) Preparation of MXene
[0102] 1.0 g of Ti3AlC2 was added to a mixed etchant solution consisting of 6 mL HCl, 6 mL HF, and 6 mL deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 ° C for 8 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 4 times, and dried at 50 ° C for 5 h to obtain an accordion-shaped MXene.
[0103] (2) Preparation of MXene-MOFs heterostructures
[0104] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.2 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.2 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 80°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.8:0.2, respectively.
[0105] Example 7
[0106] 1) Preparation of MXene
[0107] 0.7 g of Ti3AlC2 was added to a mixed etchant solution consisting of 7 mL HCl, 7 mL HF, and 7 mL deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 60 ° C for 13 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 3 times, and dried at 50 ° C for 8 h to obtain an accordion-shaped MXene.
[0108] (2) Preparation of MXene-MOFs heterostructures
[0109] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.4 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.4 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 80°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.6:0.4, respectively.
[0110] Example 8
[0111] 1) Preparation of MXene
[0112] 0.8 g of Ti3AlC2 was added to a mixed etchant solution consisting of 8 mL HCl, 8 mL HF, and 8 mL deionized water (DI water) (HCl: HF: DI water = 1:1:1). The mixture was stirred at 70 °C for 12 h. The product was then repeatedly washed with DI water until the pH was neutral, centrifuged 5 times, and dried at 50 °C for 5 h to obtain an accordion-shaped MXene.
[0113] (2) Preparation of MXene-MOFs heterostructures
[0114] The product obtained in (1) was dissolved in 10 ml of DMF and stirred to obtain a uniform system. Then 0.2 g of copper chloride was added to the mixed solution and stirred evenly to obtain a uniform system. Then 0.2 g of H2BDC was added and stirred until it was completely dissolved and mixed with Cu 2+ The mixed solution was then transferred to a reactor, and after the reaction was completed, the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 80°C for 12 hours to obtain a MXene-MOFs heterostructure with a MXene:MOFs content of 0.8:0.2, respectively.
[0115] Example 9 Construction of NH3 Gas Sensor
[0116] (1) Using the interdigital electrode as the gas sensing electrode, the MXene-MOFs heterostructure gas sensing material prepared in Example 1 was added to 5 mL of water and mixed to form a uniform slurry. Then 10 μL of the slurry was dropped on the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrode was dried at 80°C to form a sensing film.
[0117] (2) The electrode obtained in step (1) is then heated in an oven to 200° C. for 2 hours to remove the residual organic solvent, thereby obtaining an NH 3 gas sensor.
[0118] Example 10 Construction of NH3 gas sensor
[0119] (1) Using the interdigital electrode as the gas sensing electrode, the MXene-MOFs heterostructure gas sensing material prepared in Example 3 was added to 5 mL of anhydrous ethanol and mixed to form a uniform slurry. Then 5 μL of the slurry was dropped on the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrode was dried at 60°C to form a sensing film.
[0120] (2) The electrode obtained in step (1) is then heated to 180° C. in an oven for 2 hours to remove the residual organic solvent, thereby obtaining an NH 3 gas sensor.
[0121] Embodiment 11
[0122] The NH3 gas sensors prepared in Examples 9 and 10 are applied to the detection of NH3 gas molecules, and the steps are as follows:
[0123] (1) Preparation of gas sensing electrode: The NH3 gas sensor constructed in Example 9 was used as the working electrode;
[0124] (2) Standard gas configuration: To obtain the required gas, NH3 liquid was added into the test chamber using a micro syringe and evaporated directly;
[0125] (3) Working curve drawing: The electrodes described in (1) are connected to the gas sensor detection equipment, and the gas distribution method described in (2) is used in the gas chamber; the resistance of the sensor before and after ventilation is tested in the chamber with relative humidity (RH = 25%) and constant temperature (determined according to the sensor working temperature); the working curve is drawn based on the relationship between the resistance change and the NH3 concentration; the resistance change is measured by R g / R a Indicates that R a refers to the resistance in ambient air, while R g is the resistance in the measured gas; the working curve takes the concentration of NH3 gas molecules as the horizontal axis, R g / R a is plotted as the vertical axis. Figure 1It can be seen that the sensor shows a good linear range for NH3.
[0126] Example 12
[0127] Inject interfering gas molecules with the same concentration as NH3 into the chamber, test their gas-sensitive properties, and obtain the selectivity of the sensor. (The test method and test conditions are consistent with NH3 gas detection); Figure 2 It can be seen that the sensor has good selectivity for NH3 molecules.
[0128] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a MXene-MOFs heterostructure material, characterized in that: The preparation method comprises the following steps: (1) A mixture containing Ti3AlC2 and an etchant is stirred, washed, centrifuged, and dried to obtain an accordion-shaped MXene; (2) The obtained mixture II of accordion-shaped MXene, Cu precursor, H2BDC, and solvent is reacted, centrifuged II, washed II, and dried II to obtain a MXene-MOFs heterostructure material.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of the Ti3AlC2 to the etchant is 0.5-1 g: 10-50 mL; Preferably, the etchant comprises HCl, HF and water; Preferably, the volume ratio of HCl, HF and water is 1:1:
1.
3. The preparation method according to claim 1, characterized in that: In the step (2), the Cu precursor is selected from at least one of copper chloride, copper acetylacetonate, copper acetate, and copper nitrate; Preferably, the mass ratio of the Cu precursor to the H2BDC is 0.5:1 to 1:0.5; Preferably, the mass volume ratio of the accordion-shaped MXene to the solvent is 0.5-1 g: 0.5-1 mL; Preferably, the mass ratio of the accordion-shaped MXene to the Cu precursor is 1:
1.
4. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of ethanol, N,N-dimethylformamide and methanol; Preferably, the solvent is N,N-dimethylformamide, and the amount of N,N-dimethylformamide used is 10 to 25 mL.
5. The preparation method according to claim 1, characterized in that: In the step (1), the stirring temperature is 40 to 90° C. and the stirring time is 16 to 24 hours; Preferably, in step (2), the reaction temperature is 50 to 100° C., and the reaction time is 12 to 24 hours.
6. The preparation method according to claim 1, characterized in that: The temperatures of drying I and drying II are independently selected from 50 to 85° C., and the times of drying I and drying II are independently selected from 6 to 12 hours; Preferably, the number of centrifugation I and centrifugation II is independently selected from 3 to 7 times; Preferably, the solvents for washing I and washing II are independently selected from at least one of water, ethanol and methanol.
7. The MXene-MOFs heterostructure material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The MXene-MOFs heterostructure material has a two-dimensional lamellar structure.
8. The MXene-MOFs heterostructure material according to claim 7, characterized in that: The content ratio of MXene to MOFs in the MXene-MOFs heterostructure material is 1:5% to 30%.
9. Use of the MXene-MOFs heterostructure material according to any one of claims 7 to 8 in an NH3 gas sensor.
10. The use according to claim 9, characterized in that: The detection limit of the NH3 gas sensor for NH3 is 460-600 ppb; Preferably, the operating temperature of the NH3 sensor is 25-35°C.
Citation Information
Patent Citations
Preparation method of hybrid material, hybrid material and application of hybrid material
CN106513056A
Preparation method of polyaniline hollow sphere / MXene composite ammonia gas sensitive material
CN113340947A
Flexible film electrode and preparation method and application thereof
CN114875429A
TiO2 / MXene / MOFs photocatalytic material and preparation method thereof
CN114985011A
Composite wave-absorbing material prepared by deriving MXene / heterogeneous metal MOFs and method thereof
CN116751562A
Cited By
MXene doped silver modified mesoporous MEL molecular sieve composite material, electrochemical sensor and preparation method and application of MXene doped silver modified mesoporous MEL molecular sieve composite material
CN121292464A
Bimetal conductive MOF-based gas sensitive material, preparation method and semiconductor sensor
CN121453859A